Agent-Mediated Electronic Commerce. Designing Trading Strategies and Mechanisms for Electronic Markets AMEC 2011, Taipei, Taiwan, May 2, 2011, and TADA 2011, Barcelona, Spain, July 17, 2011, Revised Selected Papers - David, Esther; Robu, Valentin; Shehory, Onn; Stein, Sebastian; Symeonidis, Andreas (Springer eBooks, 2013)
This volume contains ten thoroughly refereed and revised papers detailing recent advances in research on designing trading agents and mechanisms for agent-mediated e-commerce. They were originally presented at the 13th International Workshop on Agent-Mediated Electronic Commerce (AMEC 2011), collocated with AAMAS 2011 in Taipei, Taiwan, or at the 2011 Workshop on Trading Agent Design and Analysis (TADA 2011), collocated with IJCAI 2011 in Barcelona, Spain. The papers presented at these two workshops illustrate both the depth and broad range of research topics in this field. They range from providing solutions to open theoretical problems in online scheduling and bargaining under uncertainty, to designing bidding agents in a wide area of application areas, such as electronic commerce, supply chain management, or keyword advertising, to designing agents that can successfully replicate actual human behaviors in realistic games.